Effect of flocculation aids on the electric field assisted dewatering of solid liquid systems - Jami, Mohammed Saedi; Iwata, Masashi; Alam, Md. Monjurul; Alam, Md. Zahangir (2014)
Various construction techniques such as tunnel construction and earth drilling result in the production of huge amount muddy water with a high solid-to-liquid ratio. Consequently there is a need for disposing these large quantities of muddy wastewater. Dewatering by conventional belt press filters can achieve only small solids contents leading to high expenditure for the transport and disposal of these materials. Another option is the incineration. But since the water content is usually very high, energy consumption is the major concern. In this study, constant-current electroforced sedimentation (EFS) of zinc oxide is analyzed using the Terzaghi–Voigt combined model by neglecting the creep deformation of the material and the effect of adding dewatering aids on the enhancement of water removal is investigated. High current density yields higher dewatering. Increase in initial solid content slightly improves the effectiveness of dewatering. The addition of polyacrylamide as a dewatering aid enhanced the electroforced sedimentation.